The Anthropology of Parliaments Entanglements in Democratic Politics - Crewe, Emma (Taylor & Francis, 2021)
The Anthropology of Parliaments offers a fresh, comparative approach to analysing parliaments and democratic politics, drawing together rare ethnographic work by anthropologists and politics scholars from around the world. Crewe's insights deepen our understanding of the complexity of political institutions. She reveals how elected politicians navigate relationships by forging alliances and thwarting opponents; how parliamentary buildings are constructed as sites of work, debate and the nation in miniature; and how politicians and officials engage with hierarchies, continuity and change. This book also proposes how to study parliaments through an anthropological lens while in conversation with other disciplines. The dive into ethnographies from across Africa, the Americas, Asia, Europe, the Middle East and the Pacific Region demolishes hackneyed geo-political categories and culminates in a new comparative theory about the contradictions in everyday political work. This important book will be of interest to anyone studying parliaments but especially those in the disciplines of anthropology and sociology; politics, legal and development studies; and international relations.